FOREIGN DIRECT INVESTMENT LAW IN ASEAN COUNTRIES: PROSPECT FOR ASEAN ECONOMIC COMMUNITY - bin Mohamad, Mohamad Hanapi (Yustisia, 2019)
The development of ASEAN towards the establishment of ASEAN Economic Community (AEC) at the end of 2015 has brought into sharp focus on the issue of economic and financial integration in the region. The ASEAN region has been the largest recipient of FDI, relative to GDP in Asia Pacific. Between 1952 and 2012, Singapore accounts for more than half of total FDI to the whole region. Thailand ranks the second with a 13 percent share, followed by Indonesia, Malaysia, Vietnam and the Philippines which account between 13 to 8 percent.  Foreign direct investment into ASEAN recovered from the world economic crisis and regained its 2007 level of USD 76 thousand million in 2010. ASEAN Dialogue Partners comprising EU, USA and Japan accounted USD 64 thousand million, while the share of Intra-ASEAN in this total was 16% which indicates the progress of ASEAN integration. Theories of economic integration and market liberalization have been used to explain the role of foreign direct investment in developing countries. This paper aims to examine ASEAN’s financial integration prospects. ASEAN integration could accelerate in the years ahead with enhancing financial infrastructure and reliable flexible policy frameworks. On the long term closer engagement among member countries could potentially increase real incomes and accelerate real convergence.